Improving the Lifting Capacity of Drilled Cuttings Using Henna Leaf Extracts and Lignite in Bentonite Water-based Drilling Mud - Jeffrey Onuoma Oseh; Muhammad Noorul Anam; Adams Rasyid Sidiqi (Journal of Engineering and Technological Sciences, 2019)
One of the basic functions of drilling fluids is to transport drilled cuttings to the surface. Bentonite with low solids content is preferred in carrying out this task. However, a low amount of bentonite in the drilling mud is incapable of effective cuttings lifting and suspension. In this study, a new, green, low-cost henna leaf extract and lignite in bentonite water-based drilling mud was used to transport cuttings to the surface. The effects of three hole angles (0°, 45° and 90°) were examined at different cuttings size diameters (0.5 mm, 1.0 mm, 2.0 mm and 2.4 mm) for the mud systems. The average cuttings transport efficiencies were found to be in the following order: 52-94% for 0.5 mm diameter, 45-93% for 1.0 mm diameter, 38-90% for 2.0 mm diameter, and 33-83% for 2.4 mm diameter. Viscosity and hole angle are directly related to cuttings transport efficiency. A plastic viscosity of 16 cP and yield point of 12.5 lb/100ft² were the most effective mud properties for a 45° hole angle, which needs attention while preparing the drilling mud. Addition of henna and lignite can be used to improve the rheological and filtration properties of bentonite water-based drilling mud.